Membangun Hidup Sehat Tanpa Hipertensi (Manajemen Pengendalian dan Pencegahan Hipertensi Mandiri, Mengenal Tanaman Herbal Antihipertensi, dan Membuat Suplemen Herbal Sendiri): Building a Healthy Life Without Hypertension (Self-Management of Hypertension Control and Prevention, Getting to Know Antihypertensive Herbal Plants, and Making Your Own Herbal Supplements) - Fujiati, Fujiati; Isnaini, Isnaini; Joharman, Joharman; Asnawati, Asnawati; Al Audhah, Nelly; Silapurna, Endah Labaty; Hayatie, Lisda; Setyohadi, Dwi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Hypertension is a major risk factor for cardiovascular disease, posing significant public health challenges globally. The prevalence of hypertension with uncontrolled blood pressure and its increasing number is not only caused by individual negligence but can be caused by community ignorance as a result of a lack of information on a disease. Measures to control and prevent hypertension in the community can be carried out including hypertension self-management education, introduction of antihypertensive plants, and training in making health supplements from herbs. To improve the degree of public health and knowledge of the community in the area of West Martapura Subdistrict, counseling, and training were conducted with the PKK mobilizing team of West Martapura Subdistrict using visual (electronic) media, leaflets in the form of education and demonstrations of making health supplements (fermented garlic). In this activity, the average post-test results of knowledge about self-management of hypertension prevention and control were 90.5, the average knowledge of herbal plants that have the potential as antihypertensives was 89.0 and the average post-test value of knowledge and skills in making health supplements from herbal plants in the form of fermented garlic was 84.5.